GIS for planning a sustainable and inclusive community: multi-criteria suitability analysis for siting low-income housing in a sustainable community and suitable neighborhood in Buffalo Metropolitan Area, New York. Issue 1 (February 2020) - Saleh, I; Setyowati, N D A
Abstract: This study utilized Geographic Information System (GIS) as a tool for sustainable community planning which incorporateslow-income communities into current sustainable neighborhoods. GIS suitability analysis aimed at finding suitable and sustainable neighborhoods for locating subsidized housing projects for low-income families through the Low-Income Housing Tax Credit (LIHTC) program in the Buffalo Metropolitan Area (BMA), New York. LIHTC projects allocate 30% of their rental units for low-income families. They must be located in sustainable neighborhoods to ensure economically and socially sustainable livesfor low-income inhabitants. Data was collected from various New York State government agencies and used as input for several raster-based criteria maps using GIS network analysis, raster cost-distance analysis, Kernel density analysis, raster-based local statistics, and surface analysis.The criteria of sustainable neighborhoodsusing GIS multi-criteria analysis (MCA) were grouped into five factors, namely public amenities, economic viability, population growth, property conditions, and environmental factors. A final suitability map was created by multiplying the derived raster maps with their respective weight resulting from the Analytical Hierarchical Process (AHP). The study found several locations in suburban areas of the BMA that meet the criteria and canbe usedby the Buffalo Metropolitan Housing Authority (BMHA) to site the LIHTC housing.